HEAVY METAL CONTENT IN THE SHEEP MILK - Abdrakhmanova, M. S.; Traisov, B. B. (Youth sciense-looking for the future: мaterials of the international scientific and practical conference, dedicated to the 30th anniversary of the independence of the Republic of Kazakhstan (21 мая 2021 г.)., 2021)
Many heavy metals are involved in biological processes and in certain quantities are essential for the functioning of plants, animals, and humans as trace elements. But in excessive doses it may cause serious health effects. Heavy metals are especially dangerous because of their ability to bioaccumulation: they accumulate in the body, creating an increased concentration. Since one of the main goals of agriculture is the obtaining ecologically clear product it is necessary to control the value of HM in the organism of domestic animals. In this work we investigated the concentrations of heavy metals in ewe’s milk and compared with the normal values that necessary for normal functioning.Увеличение объемов промышленного производства, использование химических веществ в сельскохозяйственных системах и другие антропогенные процессы привели к необратимому изменению экологического равновесия. Одним из таких последствий является накопление тяжелых металлов в организме животных через пищевые цепи. Многие тяжелые металлы участвуют в биологических процессах и в определенных количествах необходимы для функционирования растений, животных и человека в качестве микроэлементов. Но в чрезмерных дозах он может вызвать серьезные последствия для здоровья. Постоянное изучение и отслеживание количества загрязнения химическими добавками для обеспечения чистоты сельскохозяйственной продукции в соответствии с экологическими требованиями является одной из важнейших задач сельскохозяйственных работников.
Keywords: рк; конференции; отечественное издание; экология; тяжелые металлы; экологическое равновесие; химические добавки; влияние на животных; eavy metals; sheep; ewe’s milk